A model of multicomponent extraction process in the pulsating column; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Denisevich A. A. Aleksander Aleksandrovich; Chursin Yu. A. Yuri Alexandrovich; Kabrysheva O. P. Oksana Pavlovna; Terentev A. D. Aleksey (2016, 2016)
Title screen